Speech as "Hybrid Warfare" - Zeno-Zencovich, Vincenzo (Public Governance, Administration and Finances Law Review, 2025)
Long ago one used to say: “In a war truth is the first casualty.” The saying now should go: “In a modern war the first shot is a speech.” This paper wishes to point out how, over the last decade, informational activities have been classified as a form of “hybrid warfare” that should be countered and defeated. It analyses how traditional propaganda is now qualified as hybrid warfare and what are its consequences under international law, what does one mean for “disinformation” or “misinformation”, and how and who can determine it, as well as what are the consequences of the weaponisation of informational activity in a democratic system and in its public debate. The paper argues that a hybrid warfare is a catch-all expression which can include any kind of activity deemed as “hostile” by a country, the notion of disinformation is misleading and fuzzy, and is apt to include any sort of speech, from simple facts to statements of opinion, finally, the emphasis on hostile speech as a form of hybrid warfare has a spillover effect in domestic public debate with a powerful silencing effect on non-conventional views.